KIPPRA-IFPRI-KRA capacity sharing and working retreat on the Kenya tax model - Omune, Lensa; Mbuthia, Juneweenex (CGIAR System Organization, 2024)
Following the continues collaborative CGE modelling activities between Kenya Institute for Public Policy Research and Analysis (KIPPRA) and International Food Policy Research Institute (IFPRI), organized a capacity-sharing and working retreat focused on the Kenya Tax Model. The 10-day session began on July 29, 2024, in Naivasha, Kenya. This forms part of Kenya’s Capacity Sharing Workshops Series under the CGIAR Initiatives on National Policies and Strategies (NPS), and Foresight .The workshop brought together 8 participants from Kenya Institute for Public Policy Research and Analysis(KIPPRA) and Kenya Revenue Authority while the training was facilitated by Lensa Omune, and Juneweenex Mbuthia Research Officers based in Nairobi, Kenya office.